Lansoprazole prevents the progression of liver fibrosis in non‐alcoholic steatohepatitis model rats. (22nd January 2018) - Nishi, Toshio; Yamamoto, Yuta; Yamagishi, Naoko; Iguchi, Mikitaka; Tamai, Hideyuki; Ito, Takao; Tsuruo, Yoshihiro; Ichinose, Masao; Kitano, Masayuki; Ueyama, Takashi
Abstract: Objectives: We previously demonstrated that lansoprazole provided hepatoprotection in a drug‐induced hepatitis animal model partially through the Nrf2/HO‐1 pathway. Here, we examined whether lansoprazole could also provide hepatoprotection in a rat model of non‐alcoholic steatohepatitis (NASH). Methods: Six‐week‐old rats were fed a normal chow or a choline‐deficient amino acid‐defined (CDAA) diet to establish a rat model of NASH. The groups fed a CDAA diet for 5 weeks were subcutaneously administered either a vehicle or a lansoprazole suspension for 4 weeks beginning the second week of the experiment. Key findings: Bridging fibrosis was observed in the livers of almost all the NASH model rats (six of seven), but it was not always observed in NASH model rats (one of seven) continuously administered lansoprazole. The serum aspartate aminotransferase level elevated by the CDAA diet was significantly decreased following lansoprazole administration. Lansoprazole also increased the expression of Nrf2, but not HO‐1, in the liver of NASH model rats. Lansoprazole decreased the level of activated TGF‐β protein. Furthermore, interleukin‐6 gene and protein expression were decreased. Conclusions: Lansoprazole inhibits hepatic fibrogenesis, at least during the early stages, in CDAA diet‐induced NASH model rats. The mechanisms might be associated with cytokine suppression but not the inhibition of reactive oxygen species.